AN OBSTETRIC OUTCOME AFTER PREVIOUS SPONTANEOUS ABORTIONS - Hantodkar , Monika (Journal of Biomedical and Pharmaceutical Research, 2021)
BACKGROUND: The most frequent pregnancy problem is spontaneous pregnancy loss, which happens frequently. An estimated 50% of human pregnancies end before the first missed menstrual period, and about 70% of conceptions fail to reach viability. Any method used to end a pregnancy before the fetus is developed enough to survive is known as an abortion. RCOG states that it is twenty weeks. Nonetheless, the World Health Organization states that a fetal weight of less than 500 grams is included in the definition of abortion, and that the cutoff point for using the word is at 22 weeks gestation (154 days). An adverse modification of the current obstetric outcome due to the character of the preceding obstetric disaster is referred to as a terrible obstetric history. Since many induced abortions are not recorded, it is challenging to determine the incidence of abortion with accuracy.AIM: In women who have previously had spontaneous abortions, the study aims to quantify the probability of several unfavorable outcomes, including low birth weight, intrauterine growth restriction, stillbirth, intrauterine death, early rupture of membranes, recurrence of abortion, and any other adverse result.MATERIAL AND METHOD: 100 patients were admitted to the Medical College and Hospital's Department of Obstetrics and Gynecology in India between September 2018 and February 2020 for the purposes of this study. Random enrollment was used to select patients who had previously experienced a spontaneous abortion before becoming pregnant, regardless of their gravidity, first visit, or book. A thorough medical history was obtained, and information about prior abortions was the main focus of the assessment. These patients were seen one after the other in the same session. Every participant provided written informed permission, and the study was approved by the institutional review board. During the current pregnancy, the patients were monitored for problems such as PROM, placenta previa, preeclampsia, placental abruption, abortion, IUFD, breech, threatening abortion, and stillbirth.RESULTS: Out of 100 patients, 60 were booked and 40 were reported for the first time in an emergency. Out of the total, 60 patients belong to the age group 21-29 years, 27 in the age group < 20, 13 in the age group 30- 35, and one patient had the age of >35 years. The mode of delivery in 42% of patients was a cesarean section, followed by normal vaginal delivery in 37% and assisted vaginal delivery in 3.5% of areas.CONCLUSION: Negative pregnancy outcomes are linked to a history of spontaneous abortion; however, by providing appropriate prenatal care, the risks and fetal loss can be minimized. In uncomplicated pregnancies, serial sweeping of the membranes lowers the incidence of post-term pregnancy, its dangers, and associated expenses by preventing pregnancy beyond 41 weeks in a safe and effective manner. In cases where there have been prior abortions, the proportion of surgical deliveries rises. The history of one abortion in a prior pregnancy should be looked into and treated because it has a clear effect on the success of subsequent pregnancies.KEYWORDS: Intrauterine Growth Retardation, Inter Pregnancy Interval, Premature Rupture of Membranes, Intra uterine death and Lower Segment Caesarian Section